2021
DOI: 10.1186/s12958-021-00851-9
|View full text |Cite
|
Sign up to set email alerts
|

Icariin improves testicular dysfunction via enhancing proliferation and inhibiting mitochondria-dependent apoptosis pathway in high-fat diet and streptozotocin-induced diabetic rats

Abstract: Background Diabetes mellitus (DM), a chronic metabolic disease, severely impairs male reproductive function. However, the underpinning mechanisms are still incompletely defined, and there are no effective strategies or medicines for these reproductive lesions. Icariin (ICA), the main active component extracted from Herba epimedii, is a flavonoid traditionally used to treat testicular dysfunction. Whether ICA can improve male reproductive dysfunction caused by DM and its underlying mechanisms ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…[44] In other studies, Proanthocyanidin, icariin, and cerium oxide nanoparticles improved testicular apoptosis induced by diabetes by decreasing caspase 3 and NF-κB. [45,46] On the other hand, tropisetron inhibited F I G U R E 6 Histochemical analysis of caspase3 protein expression in different groups. (Mean ± SEM, N = 7), *compared with the control group, $ compared with the DM group (one-way ANOVA followed by Tukey's post hoc test).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[44] In other studies, Proanthocyanidin, icariin, and cerium oxide nanoparticles improved testicular apoptosis induced by diabetes by decreasing caspase 3 and NF-κB. [45,46] On the other hand, tropisetron inhibited F I G U R E 6 Histochemical analysis of caspase3 protein expression in different groups. (Mean ± SEM, N = 7), *compared with the control group, $ compared with the DM group (one-way ANOVA followed by Tukey's post hoc test).…”
Section: Discussionmentioning
confidence: 94%
“…[ 44 ] In other studies, Proanthocyanidin, icariin, and cerium oxide nanoparticles improved testicular apoptosis induced by diabetes by decreasing caspase 3 and NF‐κB. [ 45,46 ] On the other hand, tropisetron inhibited NF‐κB, caspase 3, and TNF‐α and protected amyloid‐beta‐induced neurotoxicity. [ 27 ] Moreover, Aminzadeh reported the protective effect of tropisetron on PC12 cells against high glucose‐induced apoptosis by suppressing Bax and caspase‐3 expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly to caspase-3 overexpression recorded in this study, Nna et al [42] observed caspase-3 mRNA as well as protein up-regulation, which correlated with an abrupt loss of testicular cells in STZ-induced diabetic rats. Similarly, He et al [67] commented on a significant caspase-3 positive immunocytochemical signal located primarily in Sertoli cells, spermatogonia, and spermatocytes of rats presenting with a severe hyperglycemia caused by STZ and a high fat diet. According to Ojo and Olorunsogo [18], who observed an increased release of cytochrome-c in diabetic rats, testicular apoptosis is primarily regulated by the mitochondrial pathway which corroborates our data on the BAX and Bcl-2 proteins whose interactions on the mitochondrial membrane have a decisive role in the initiation of apoptotic cell death.…”
Section: Discussionmentioning
confidence: 96%
“…Although testosterone supplementation therapy (TST) has been reported to be potentially effective for these conditions, TST has potential adverse effects (81). The effect of ICA and ICAII in increasing testosterone levels could be related to their ability to mitigate the effects of Leydig cell damage in a variety of testicular damaging environmental exposures (e.g., diabetes, toxic substances) (82,84,85). More importantly, ICA and ICAII directly increase the level of steroids (the raw material required for testosterone production) and the expression of several key enzymes in testosterone synthesis (86)(87)(88).…”
Section: Ica and Testosterone Productionmentioning
confidence: 99%